Application of wavelet-analysis for image filtration in electronic and probe microscopy - N. P. Konnov; Yu. P. Volkov; M. N. Kireev; O. S. Kuznetsov (Проблемы особо опасных инфекций, 2008)
The review presents the results of application of the programs of discrete and stationary wavelet-analysis for filtration of object image from noise and for the increase of its resolution capability in electronic and probe microscopy.